Exploring The Shadows of Recovery: A Systematic Narrative Review of Homoeopathy in Post-Covid Syndrome - S, Sheeba; M, Murugan; Sankar A.S, Suman (Journal of Neonatal Surgery, 2025)
Post-COVID syndrome (PCS) is associated with a range of ongoing physical and psychological challenges that may persist long after the acute infection phase, often proving difficult to address with standard medical approaches. Homeopathy, with its holistic and personalized methodology, is gaining relevance as a complementary therapy in long-term recovery. This review aims to assess the therapeutic potential of key homeopathic remedies, particularly Calcarea carbonica and Arsenicum album, in addressing persistent symptoms associated with PCS. It also compares these manifestations with typical upper respiratory tract infections (URTIs). A systematic narrative review was performed using academic databases such as PubMed, Scopus, Google Scholar, and AYUSH portals. Studies selected ranged from 2020 to 2024 and included peer-reviewed research, observational data, and case studies where homeopathy was used for managing PCS. Frequent symptoms included prolonged fatigue, cognitive disturbances, psychological distress, and recurring URTIs. Calcarea carbonica showed promise in supporting immune recovery and reducing exhaustion, while Arsenicum album helped alleviate anxiety and repeated infections. The review also highlighted notable clinical distinctions between PCS and seasonal URTIs, as well as estrogen's potential role in immune modulation. Individualized homeopathic approaches may offer valuable support in managing PCS symptoms. However, further randomized and controlled studies are needed to substantiate these findings and guide broader clinical integration.